2001
DOI: 10.1063/1.1386418
|View full text |Cite
|
Sign up to set email alerts
|

Phase transformations of nanometer size carbon particles in shocked hydrocarbons and explosives

Abstract: Estimates for the displacement of the phase equilibrium lines for small carbon particles containing from several hundred to several tens of thousands of atoms are made, and an error analysis of the uncertainties in these estimates is derived and evaluated using available experimental data. Hugoniot calculations for methane, benzene, polyethylene, and polybutene, based on a carbon particle surface energy adjusted equation of state, are in better agreement with shock pressure-volume and temperature data than tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
68
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(72 citation statements)
references
References 30 publications
3
68
1
Order By: Relevance
“…Aggregation of carbon atoms is determined by diffusion and proceeds in picoseconds. 33,40 At thermodynamic parameters characteristic for the detonation, the state of carbon corresponds to the condensed phase, 7,10 in contrast to other substances (N, N 2 , H 2 O, H, O, CO, CO 2 , etc.). Probability of aggregation at a collision of two carbon atoms is close to 100%, whereas reactions of gaseous substances under the detonation conditions require of order of 1000 collisions for one elementary reaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aggregation of carbon atoms is determined by diffusion and proceeds in picoseconds. 33,40 At thermodynamic parameters characteristic for the detonation, the state of carbon corresponds to the condensed phase, 7,10 in contrast to other substances (N, N 2 , H 2 O, H, O, CO, CO 2 , etc.). Probability of aggregation at a collision of two carbon atoms is close to 100%, whereas reactions of gaseous substances under the detonation conditions require of order of 1000 collisions for one elementary reaction.…”
Section: Discussionmentioning
confidence: 99%
“…The viewpoint of the existence of single particles is shared by many authors (see for example [5][6][7][8][9][10] ). In the work, 5 a dynamic model of carbon condensation at the detonation of trinitrotoluene (TNT) was proposed based on the results of the electric conductivity investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, a third parameter (surface area) becomes crucial at the nanoscale level and it become relevant in the definition of the system equilibrium energy levels: At this nano-dimensions, the Gibbs free energy becomes dependent on the contribution of the surface energy, leading to changes in the thermodynamic equilibrium phase diagram (Barnard et al, 2003;Barnard and Sternberg, 2007;Viecelli et al, 2001). Tetrahedral hydrocarbons in the form of nano-diamonds of 3 nm have been demonstrated by atomistic models to be more stable than poly-aromatics graphite (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…3), which requires high temperatures and pressures in the presence of catalyst transformation. However, an additional equilibrium parameter involving the surface becomes critical and significant for the distribution of equilibrium energy to nano size: Gibbs free energy is drastically influenced by the presence of surface energy input, modifying the phase diagram of thermodynamic equilibrium (Badziag et al, 1990;Barnard et al, 2003;Barnard and Sternberg, 2007;Viecelli et al, 2001). Atomic models have demonstrated that nanodiamonds with 3 nanometers with tetrahedric hydrocarbons are more stable than the graphite in its polyaromatic form under ambient conditions (Badziag et al, 1990;Aversa et al, 2016a;2016d;2016e).…”
Section: Introductionmentioning
confidence: 99%